Women and the Colonial State Essays on Gender and Modernity in the Netherlands Indies 1900-1942 - Locher-Scholten, Elsbeth (Amsterdam University Press, 2000)
Woman and the Colonial State deals with the ambiguous relationship between women of both the European and the Indonesian population and the colonial state in the former Netherlands Indies in the first half of the twentieth century. Based on new data from a variety of sources: colonial archives, journals, household manuals, children's literature, and press surveys, it analyses the women-state relationship by presenting five empirical studies on subjects, in which women figured prominently at the time: Indonesian labour, Indonesian servants in colonial homes, Dutch colonial fashion and food, the feminist struggle for the vote and the intense debate about monogamy of and by women at the end of the 1930s. An introductory essay combines the outcomes of the case studies and relates those to debates about Orientalism, the construction of whiteness, and to questions of modernity and the colonial state formation